Ionic composition of snow cover on the territory of Siberia and the Far East - A. V. Saltykov; S. N. Balykin; D. N. Balykin; I. V. Gorbachev (Лëд и снег)
Long-term (from 2007 to 2022) observations of the dynamics of acidity, mineralization and ionic composition of snow cover in remote mountainous and lowland landscapes of Northern Asia were carried out. As a result, spatiotemporal changes in the molar concentration of basic (Ca2+, Mg2+,HCO3-, Cl- and SO42-) and nitrogen-containing (NH4+, NO3- and NO2-) ions were analyzed. It turned out that during the entire observation period, bicarbonate ions prevailed in all monitoring regions, even near the sea coasts, where there is an intensive intake of sulfate and chloride ions into the atmosphere. Until 2012, the molar concentration of these three anions was characterized by higher values, which decreased 3–8 times in subsequent years, this is especially noticeable for bicarbonate ions and to a lesser extent for chloride ions. The molar concentration of nitrogen-containing ions in the snow cover of Northern Asia was at a low level (especially nitrite ions). Ammonium ions were predominant throughout the observation period (especially in mountainous landscapes) and only in some years – nitrate ions.